Pengembangan Materi Video Pembelajaran dengan OpenShot untuk Meningkatkan Kompetensi Digital Guru Sekolah Dasar - Sri Hapsari Wijayanti; Clara Ika Sari Budhayanti; Margaretha Susanti; Veronica Veronica; Andriani Wiyesi (Universitas Muhammadiyah Surakarta, 2023)
Learning by video makes teachers explain complex or conceptual material, motivate students, create a less boring learning atmosphere, and students can repeat watching videos to understand the material better. The skills of making and editing videos for classroom needs have not been mastered yet by elementary school teachers in Cisauk Subdistrict, Tangerang. This community service activity aims to develop the digital competence of elementary school teachers in Cisauk District through training on making learning video materials using OpenShot Video Editor. The participants were 20 people from 12 public elementary schools. The methods used are training, assignment or project, mentoring, monitoring, and evaluation. The training was delivered online and offline, with one meeting each. Assistance and monitoring of video assignments were carried out online for three meetings. The results of the evaluation were observed from the resulting videos and interviews. This training provides the teachers with new knowledge, insights, and skills. The teachers are not used to editing videos yet. The videos produced by teachers still need to be improved and prepared carefully, including by utilizing mentoring to discuss the video-making process and prepare storyboards better